2020
DOI: 10.7554/elife.57341
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic-scale functional networks in the primate amygdala

Abstract: The primate amygdala performs multiple functions that may be related to the anatomical heterogeneity of its nuclei. Individual neurons with stimulus- and task-specific responses are not clustered in any of the nuclei, suggesting that single-units may be too-fine grained to shed light on the mesoscale organization of the amygdala. We have extracted from local field potentials recorded simultaneously from multiple locations within the primate (Macaca mulatta) amygdala spatially defined and statistically separabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This results in a single time series from each region, which was subjected to further analyses. We and others have shown that this method increases signal-to-noise characteristics while reducing computational costs and multiple-comparisons issues, and is more accurate than other sources separation methods such as principal components analysis and independent components analysis in M/EEG and LFP data (Haufe et al, 2014 ; de Cheveigné and Arzounian, 2015 ; Cohen, 2017a ; Morrow et al, 2020 ). An advantage of generalized eigendecomposition over independent components analysis is that it optimizes the spatial filter for narrowband activity, which was a primary goal here.…”
Section: Methodsmentioning
confidence: 91%
“…This results in a single time series from each region, which was subjected to further analyses. We and others have shown that this method increases signal-to-noise characteristics while reducing computational costs and multiple-comparisons issues, and is more accurate than other sources separation methods such as principal components analysis and independent components analysis in M/EEG and LFP data (Haufe et al, 2014 ; de Cheveigné and Arzounian, 2015 ; Cohen, 2017a ; Morrow et al, 2020 ). An advantage of generalized eigendecomposition over independent components analysis is that it optimizes the spatial filter for narrowband activity, which was a primary goal here.…”
Section: Methodsmentioning
confidence: 91%
“…Our classifiers are trained on data obtained from different subject and sessions when the linear probes recorded neural activity from different nuclear subdivisions of the amygdala. In fact, the classifiers do not generalize when applied to data obtained from other sessions, which was expected based previous work that mapped dissociable functions to different mesoscale subregions of the amygdala (Morrow et al, 2019). For the purpose of this paper, our (non-generalizable) approach was sufficient to conclude that contextual information is present in baseline LFP.…”
Section: Discussionmentioning
confidence: 72%
“…While less is known about interactions within the MTL, our data indicate that a similar mechanism might be used to coordinate information flow between the amygdala and hippocampus. The non-human primate amygdala contains multiple putative subnetworks indexed by distinct neural coactivity patterns that are characterized by different dominant frequencies in 0- to 20-Hz range ( 61 ).…”
Section: Discussionmentioning
confidence: 99%